Empowerment Model on Adolescent Social Capital for Smoking Cessation Behavior in Sumenep, East Java - Riyadi, Sujono; Utami, Khristina Dias; Al Madury, Shalahuddin; Farid, Muhammad (YCAB Publisher, 2025)
Background: Smoking is one of the risk factors for increasing morbidity and premature mortality worldwide. The large number of teenagers who smoke makes smoking the second largest contributor to global disability adjusted for life years with 148 million cases each year. Objective: This study aims to test a social empowerment model for adolescents to quit smoking, by exploring the influence of variables related to smoking cessation behavior among adolescents. Method: This study used a descriptive analytical design with a cross-sectional approach, involving 200 adolescents aged 12-25 years in Sumenep Regency, Madura. The structured questionnaire used to collect data has been validated. The analysis was carried out with descriptive statistics and path analysis using the STATA 13 to evaluate the effect of variables on smoking cessation behavior. Results: The study showed that out of 200 adolescents, 66% had a strong intention to quit smoking. Positive attitudes, subjective norms, and perceived behavioral control significantly influenced the intention to quit smoking. Adolescents with high knowledge about the dangers of smoking and strong social capital from peers also showed higher intentions. Path analysis indicated that the intention to quit smoking was the main mediator by the influence of attitudes, norms, and knowledge on smoking cessation behavior, with a p-value <0.001 indicating high significance. Conclusion: The smoking cessation behavior adolescents is influenced by intention to quit smoking, positive attitudes, subjective norms, perceived control, and knowledge about the dangers of smoking. Social capital from peers plays an important role in increasing this intention. The implications of the results of this study emphasize the need for education-based interventions and social support to reduce smoking habits among adolescents. Keywords: Social capital; adolesent; smoking cessation